Eosinophilic Inflammation in COPD: Mechanisms, Diagnostic Markers, Clinical Features and Therapy Guidance - Aigerim Aitkazina; Natalya Latypova; Meirzhan Abishev; Aleksey Pak; Nurmakhan Zholshybek; Samat Suleimenov; Madi Malik (National Scientific Medical Center, 2024)
Chronic obstructive pulmonary disease (COPD) is one of the main causes of morbidity and mortality worldwide. Eosinophilia, which may have a significant role in the inflammation process and obstruction of airways, is present in about one third patients suffering from COPD. The significance of eosinophil counts in COPD is currently debated, but they can potentially serve as biomarkers for treatment selection. Blood eosinophil counts can assist in determining the patients who can benefit from inhaled corticosteroid therapy to prevent or eliminate exacerbations. The aim of this review is to demonstrate the significance of eosinophilic inflammation COPD and the use of eosinophilic inflammation biomarkers to guide therapy decisions. To reach this goal, a search of relevant literature on the subject was conducted. Articles were searched in electronic sources: PubMed and Google Scholar. The keywords "COPD and eosinophilia", "COPD exacerbations and eosinophilia", "inhaled corticosteroids, COPD and eosinophilia" were used. One hundred and twenty sources were found, of which 66 were selected. Results of the review showed high frequency of eosinophilic phenotype detection in COPD. Blood eosinophilia becomes a potential universal marker of eosinophilic COPD. Blood eosinophils level can predict response to inhaled corticosteroids treatment patients with COPD, but increases the likelihood of pneumonia. Overall, the role of eosinophilia in COPD has not been obtained to date, which suggests it needs further study.